Production of green diesel from saturated chicken fat oil catalyzed by binary metal oxide supported on multi-walled carbon nanotubes - Nasharuddin, Nurul Aliana (2020)
Fossil fuels have been the most important energy and fuel sources over centuries. However, there has been growing distressed regarding on energy crisis caused by the oil reserve depletion and the effect of environmental issues (e.g. acid rain and global warming). Due to the high demand for energy, renewable energy has gained extensive attention worldwide in the past ten years as alternative energy to replace fossil fuels. In particular, fuels obtained from biomass (biofuels) has become a great option as a sustainable substitute for fossil fuels. Deoxygenation processes that exploit milder reaction conditions under H2-free atmospheres appear environmentally and economically effective for the production of green diesel. However, the presence of a catalyst in the deoxygenation reaction is important to excite optimum catalytic activity of the synthesized catalyst for a specific reaction system. The catalyst support plays an essential role in synthesizing catalyst, which is to improve the interaction between active metal-support, promoting active metal dispersion on the surface and providing the adequate active site. Herein, green diesel was produced by catalytic deoxygenation of chicken fat oil (CFO) over oxides of binary metal pairs (Ni–Mg, Ni–Mn, Ni–Cu, Ni–Ce) supported on multi-walled carbon nanotubes (MWCNTs). The yield of hydrocarbons are arranged in the order of blank < MWCNT < Ni₁₀/MWCNT < Ni₁₀-Mn₁₀/MWCNT < Ni₁₀-Cu₁₀/MWCNT < Ni₁₀-Mg₁₀/MWCNT < Ni₁₀-Ce₁₀/MWCNT. The deoxygenation reaction will lead to the formation of C15 and C17 of diesel fractions as the main product. Thus, the n-(C15+C17) selectivity are arranged in the increasing order of blank < MWCNT ~ Ni₁₀-Cu₁₀/MWCNT < Ni₁₀-Ce₁₀/MWCNT < Ni₁₀-Mn₁₀/MWCNT < Ni₁₀-Mg₁₀/MWCNT < Ni₁₀/MWCNT. The result shows that Ni₁₀/MWCNT has highest n-(C15+C17) selectivity but with low hydrocarbon yield due to its favor toward cracking-decarboxylation/decarbonylation (deCOx) reaction. Therefore, presence of Mg and Mn with Ni seems effective in deoxygenation activity, with hydrocarbon yields of >75% and n-(C15+C17) selectivity of >81%, indicating that deCOx of CFO is favored by the existence of the high amount of lower strength strong acidic sites along with noticeable strongly basic sites. Based on a series of studies of different Mg and Mn dosages (5–20 wt %), the oxygen free-rich diesel-range hydrocarbons produced efficiently by Ni10-Mg15/MWCNT and Ni10-Mn5/MWCNT catalysts yielded >84% of hydrocarbons, with n-(C15+C17) selectivity of >85%. The findings reveal that Ni10-Mg15/MWCNT shows high resistancy toward coke formation (coke < 5 wt %) under TGA analysis. In addition, Ni10-Mg15/MWCNT shows high catalytic stability and reusability up to 5 cycles with >73% of yield and n-(C15+C17) selectivity of >66%.